Integration of Service Quality and Sustainability on Revisit Intention - Dwi, Doni Nugroho; Pujiyanto, Eko; Damayanti, Retno Wulan (Jurnal Kesehatan Vokasional, 2025)
Background: Hospital service quality played an important role in improving patient satisfaction and loyalty. However, sustainability, particularly the triple bottom line, became a new challenge in modern hospital management. Several studies demonstrated significant influences of service quality and sustainability on patients' intentions to revisit, yet studies that systematically integrated both aspects, especially in specialist hospitals, remained limited.Objective: This study aimed to examine the relationship between service quality dimensions and sustainability in relation to patient satisfaction and revisit intention, as well as to formulate future research agendas concerning sustainable healthcare services.Methods: Literature was collected using the PRISMA method from the Scopus and Google Scholar databases, covering publications from 2019 to 2025.Results: The analysis indicated that most of the reviewed literature employed the PLS-SEM method to examine the relationship between service quality and patient satisfaction. The findings consistently showed that service quality dimensions affected patient satisfaction, while sustainability dimensions contributed significantly to service perception and patients’ revisit intention. However, studies examining the integration of service quality and the triple bottom line remained scarce.Conclusion: The integration of service quality and sustainability emerged as an important aspect in improving service quality and patient retention. This study provided direction for future research and hospital practices aiming to develop value-oriented service systems with long-term and operational sustainability.